Edgewise compression of composite sandwich panels: effect of core hybridization - Tarlochan, Faris; Hamouda, Abdel Magid Salem; Sahari, Barkawi; Saad, Elsadig Mahdi Ahmed (Universiti Putra Malaysia Press, 2005)
The behavior of polymer composite sandwich panels subjected to quasi-static edgewise compression is examined experimentally, in order to evaluate the load-carrying capacity and energy absorption capability of such composite structures. Series of experiments were performed for the sandwich panels with different core thicknesses and material combinations. Experiments showed that the panels tested failed primarily in a buckling manner. Nonetheless, significant enhancement in load carrying capacity and energy absorption capability was found when rigid foam was used. The data provided from this study will be important for designing sandwich panels for buckling and crashworthiness application.